Hard coating film and image display device including the same

By introducing fluorine-based UV-curable functional groups, fluorine-based UV-curable compounds, hollow silica particles and nano-silica particles into the hard coat of the image display device, a low-refractive layer is formed, which solves the problem of optical properties degradation of the hard coat after improving durability, and achieves reflectivity control and improvement of mechanical properties.

CN120641510APending Publication Date: 2025-09-12DONGWOO FINE CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480011160.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-09
Filing Date
2024-01-23
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

After the durability of the hard coating film of the existing image display device is improved, the optical properties such as refractive index and reflectivity may be reduced, making it difficult to maintain excellent mechanical and optical properties at the same time.

Method used

A low-refractive layer containing a compound containing a fluorine-based UV-curable functional group, hollow silica particles, and nano-silica particles is used to control the reflectivity of the hard coating film to be above 2% and less than 3%, and a laminated structure of the hard coating layer and the low-refractive layer is formed on the substrate.

Benefits of technology

The reflectivity is controlled within an appropriate range, while the mechanical properties of the hard coating, such as the initial water contact angle, anti-fogging, scratch resistance and wear resistance, are improved, thereby enhancing the optical and physical properties of the image display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120641510A_ABST
    Figure CN120641510A_ABST
Patent Text Reader

Abstract

The present invention relates to a hard coating film and an image display device comprising the same, the hard coating film comprising a hard coating layer and a low refractive layer formed on the hard coating layer, the low refractive layer being formed from a composition for forming a low refractive layer, the composition for forming the low refractive layer contains a compound containing a fluorine-based UV-curable functional group, hollow silica particles, and nanosilica particles, the thickness of the low refractive layer is 50-200 nm, and the value of formula 1 is 90-150%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hard coating film and an image display device including the same. Background Art

[0002] Recently, image display devices such as liquid crystal display (LCD) devices and organic light emitting display (OLED) devices have been steadily becoming thinner and more flexible. These image display devices are suitable not only for smartphones and tablet PCs, but also for a wide range of smart devices characterized by portability, such as various wearable devices.

[0003] Such image display devices include additional functional layers on one or both sides of a substrate such as glass or resin in order to impart transparency, durability such as hardness, mechanical properties such as bending properties, and / or antifouling properties, as well as optical properties.

[0004] Korean Patent Gazette No. 10-2444443 provides a flexible window cover film having improved physical properties by including a hard coating layer to adapt to flexible characteristics such as bending resistance, pencil hardness, and elastic recovery rate. However, there is a problem that the optical characteristics related to the refractive index or reflectivity may be reduced due to the improved durability.

[0005] Therefore, there is a real need to develop a hard coat film capable of controlling the refractive index and reflectivity to achieve excellent optical characteristics and durability, and a display device including the same. Summary of the Invention

[0006] Technical issues

[0007] In order to solve the above problems, an object of the present invention is to provide a hard coat film having improved optical properties by controlling the reflectance of the hard coat film to 2% or more and less than 3%, and an image display device including the same.

[0008] Another object of the present invention is to provide a hard coat film having a reflectance adjusted to the above range and excellent mechanical properties, and an image display device including the same.

[0009] However, the problems to be solved by the present invention are not limited to the problems mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description.

[0010] Solution to the problem

[0011] The present invention relates to a hard coating film, characterized in that it comprises: a hard coating layer and a low-refractive layer formed on the hard coating layer, wherein the low-refractive layer is formed from a low-refractive layer-forming composition, the low-refractive layer-forming composition comprising a compound containing a fluorine-based UV-curable functional group, hollow silica particles, and nano-silica particles, the low-refractive layer has a thickness of 50 to 200 nm, and the value of the following formula 1 is 90 to 150%.

[0012] [Formula 1]

[0013] (B / A)*100(%)

[0014] (In the above formula 1, A is the average particle size of the hollow silica particles contained in the low-refractive layer-forming composition, and B is the average particle size of the nano-silica particles contained in the low-refractive layer-forming composition.)

[0015] In the present invention, the compound containing a fluorine-based UV-curable functional group may have 1 to 6 UV-curable functional groups in the molecule.

[0016] The present invention may be characterized in that the reflectance of the hard coat film is 2% or more and less than 3%.

[0017] In the present invention, the hard coat layer and the low-refractive layer may be formed on one or more substrates selected from release films formed from polyester resins, polyamide resins, acrylic resins, styrene resins, polycarbonate resins, polylactic acid resins, polyurethane resins, polyolefin resins, vinyl resins, polyamide resins, sulfone resins, polyether-ether-ketone resins, allyl compound resins, cellulose resins, and mixtures thereof.

[0018] The low-refractive-refractive-layer-forming composition of the present invention may further contain one or more kinds selected from the group consisting of a light-transmitting resin, an initiator, and a solvent.

[0019] The present invention may be characterized in that the hollow silica particles have a refractive index of 1.17 to 1.40.

[0020] The present invention may be characterized in that the hollow silica particles are contained in an amount of 0.1 to 20 parts by weight based on 100 parts by weight of the entire composition for forming a low-refractive layer.

[0021] The present invention may be characterized in that the average particle size of the nano-silica particles is 80 to 130 nm.

[0022] The low-refractive-refractive-layer-forming composition of the present invention may contain, as an additive, one or more kinds selected from the group consisting of a leveling agent, an ultraviolet stabilizer, and a heat stabilizer.

[0023] Furthermore, the present invention may relate to an image display device including the hard coat film.

[0024] Effects of the Invention

[0025] With the hard coating film according to the present invention, the reflectivity can be controlled to be greater than 2% and less than 3%.

[0026] Furthermore, the hard coating film according to the present invention has the characteristics of a high initial water contact angle, haze prevention, excellent scratch resistance and abrasion resistance, thereby providing a hard coating film having excellent physical and / or optical properties and an image display device including the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A diagram showing a laminated structure of a base material layer including a hard coating film and a base material according to one embodiment of the present invention.

[0028] The symbols in the accompanying drawings are as follows:

[0029] 100: base material layer

[0030] 110: Base material

[0031] 120: Hard coating

[0032] 121: Hard coating

[0033] 122: Low refractive layer DETAILED DESCRIPTION

[0034] The present invention relates to a hard coat film comprising a hard coat layer formed on a substrate and a low-refractive layer formed on the hard coat layer, and an image display device including the same. The hard coat film is characterized in that its reflectivity can be controlled to be between 2% and 3% while maintaining excellent mechanical properties.

[0035] More specifically, the low-refractive layer is formed from a low-refractive layer-forming composition, the low-refractive layer-forming composition comprising a compound containing a fluorine-based UV-curable functional group, hollow silica particles, and nano-silica particles. The thickness of the low-refractive layer is 50 to 200 nm, the value of the following formula 1 may be 90 to 150%, and the hard coat layer-forming composition of at least one of the hard coat layer and the low-refractive layer may comprise a compound containing a fluorine-based UV-curable functional group.

[0036] [Formula 1]

[0037] (B / A)*100(%)

[0038] In the above formula 1, A is the average particle size of the hollow silica particles contained in the low-refractive layer-forming composition, and B is the average particle size of the nano-silica particles contained in the low-refractive layer-forming composition.

[0039] According to one embodiment of the present invention, the hard coating film has a reflectivity of 2% or more and less than 3% and is capable of maintaining excellent mechanical properties. This advantage is likely due to the structural characteristics of including a compound containing a fluorine-based UV-curable functional group in the low-refractive layer and having an average particle size ratio of 90 to 150% between the nano-silica particles and the hollow silica particles. Including the hard coating film of the present invention can provide a hard coating film having excellent physical properties such as a high initial water contact angle, anti-fogging, scratch resistance, and abrasion resistance, and / or an image display device having excellent optical properties including the hard coating film.

[0040] The following describes embodiments of the present invention in more detail with reference to the accompanying drawings. However, the drawings in this specification are intended to illustrate preferred embodiments of the present invention and, together with the above-described disclosure, contribute to a deeper understanding of the technical concept of the present invention. Therefore, the present invention should not be construed as being limited solely to the matters depicted in these drawings.

[0041] The terms used in this specification are used to illustrate the embodiments and are not intended to limit the present invention. In this specification, unless otherwise specified, the singular includes the plural. For example, the term "hard coating" used in this specification may refer to at least one of a hard coating and a low-refractive layer.

[0042] The terms "comprises" and "comprising" used in this specification do not exclude the existence or addition of one or more other constituent elements, steps, actions and / or devices other than the mentioned constituent elements, steps, actions and / or devices. The same reference numerals throughout the specification represent the same constituent elements.

[0043] As used herein, "substantially" should be interpreted as meaning not only physically identical or identical but also within the margin of error in measurement and manufacturing processes. For example, it can be interpreted as meaning a margin of error of 0.1% or less. Furthermore, in the present invention, "transparent" means a visible light transmittance of 70% or greater or 80% or greater.

[0044] <Hard Coat>

[0045] Reference Figure 1According to one embodiment of the present invention, the hard coating film 120 may include a hard coating layer 121 and a low-refractive layer 122 formed on the hard coating layer. More specifically, the hard coating film 120 of the present invention is formed on a substrate 110. The low-refractive layer is formed from a low-refractive layer-forming composition, which contains a compound containing a fluorine-based UV-curable functional group, hollow silica particles, and nano-silica particles. The thickness of the low-refractive layer is 50 to 200 nm, and the value of the following formula 1 satisfies 90 to 150%. This allows the reflectivity of a display device including the hard coating film to be controlled within a range of 2 to 3%, thereby providing an image display device with improved optical properties and excellent mechanical properties. More specifically, by sequentially stacking the hard coating layer and the low-refractive layer of the present invention on a substrate, the reflectivity of the film is reduced, the transmittance is increased, and the brightness can be increased, thereby having the advantage of reducing battery power consumption. In the case of hollow silica, the higher the content of nano-silica particles, the lower the refractive index, and thus the reflectivity may be reduced, but there is a disadvantage of reduced mechanical properties. However, the hard coating film according to one embodiment of the present invention includes a compound containing a fluorine-based UV-curable functional group, hollow silica particles, and nano-silica particles in the low-refractive layer-forming composition, thereby reducing the reflectivity and increasing the hardness, thereby improving the mechanical properties.

[0046] Furthermore, the hard coat film according to the present invention is characterized in that it is formed in direct contact without including a separate base layer for bonding to the hard coat layer, thereby simplifying the production process compared to conventional laminates.

[0047] [Formula 1]

[0048] (B / A)*100(%)

[0049] In the above formula 1, A is the average particle size of the hollow silica particles contained in the low-refractive layer-forming composition, and B is the average particle size of the nano-silica particles contained in the low-refractive layer-forming composition.

[0050] Hard coating 121

[0051] The hard coat layer 121 can be made from a hard coat layer-forming composition. Specifically, the hard coat layer-forming composition can include one or more selected from the group consisting of a light-transmitting resin, an initiator, and a solvent, and can further include additives. The additives can include one or more selected from the group consisting of a leveling agent, a UV stabilizer, and a heat stabilizer. In addition, other known components included in the hard coat layer composition in the art can be included without limitation within the scope that does not affect the purpose and effect of the present invention.

[0052] The hard coating layer 121 is formed on a substrate 110, which will be described later. According to one embodiment of the present invention, the hard coating layer 121 can be produced by applying a hard coating layer-forming composition to the substrate 110 and then curing the composition using light or heat. The hard coating layer-forming composition of the present invention can have excellent adhesion to the substrate 110 and can improve mechanical properties such as hardness, scratch resistance, antifouling properties, wear resistance, chemical resistance, and flex resistance.

[0053] Translucent resin

[0054] The light-transmitting resin used for forming the hard coat layer of the present invention contains a photopolymerizable functional group and may be a photopolymerizable monomer, a photopolymerizable oligomer, or the like. For example, it may be a photoradical polymerizable compound.

[0055] As the photopolymerizable monomer, any monomer used in the art having an unsaturated group such as a (meth)acryloyl group, a vinyl group, a styryl group, an allyl group, or the like, which is a commonly used photocurable functional group in the molecule, can be used without limitation. More specifically, monofunctional and / or polyfunctional (meth)acrylates can be mentioned. These can be used alone or in combination of two or more.

[0056] In the present invention, "(meth)acrylic acid-" means "methacrylic acid-", "acrylic acid-" or both.

[0057] Specific examples of the (meth)acrylate monomer include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerol tri(meth)acrylate, tris(2-hydroxyethyl)isocyanate tri(meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol (meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, bis(2-hydroxyethyl)isocyanate di(meth)acrylate, and poly(meth)acrylates obtained by adding ethylene oxide or propylene oxide to the above (meth)acrylates; and Oligomeric ester (meth)acrylates, oligomeric ether (meth)acrylates, oligomeric urethane (meth)acrylates, and oligomeric epoxy (meth)acrylates having 1 to 3 (meth)acryloyl groups; hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and products obtained by adding ethylene oxide or propylene oxide to the above (meth)acrylates; and monomers having trifunctional or less (meth)acryloyl groups, such as mono(meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, stearyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and phenoxyethyl (meth)acrylate; and dipentaerythritol hexa(meth)acrylate, dipentaerythritol hydroxypenta(meth)acrylate, pentaerythritol tetra(meth)acrylate, and ditrimethylolpropane tetra(meth)acrylate. These may be used alone or in combination of two or more.

[0058] The photopolymerizable oligomer may be, for example, one or more selected from the group consisting of epoxy (meth)acrylates, urethane (meth)acrylates, and polyester (meth)acrylates. Specifically, a urethane (meth)acrylate and a polyester (meth)acrylate may be mixed, or two polyester (meth)acrylates may be mixed. In order to improve the scratch resistance and hardness of the cured product and increase the elastic modulus of the hard coat layer, it is preferred to include a urethane (meth)acrylate oligomer.

[0059] The urethane (meth)acrylate can be produced by reacting a polyfunctional (meth)acrylate having a hydroxyl group in its molecule with a compound having an isocyanate group in the presence of a catalyst using a method known in the art.

[0060] Specific examples of the polyfunctional (meth)acrylate having a hydroxyl group in the molecule may be one or more selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxyisopropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone ring-opening hydroxy acrylate, a pentaerythritol tri / tetra(meth)acrylate mixture, and a dipentaerythritol penta / hexa(meth)acrylate mixture.

[0061] Specific examples of the compound having an isocyanate group include 1,4-diisocyanatobutane, 1,6-diisocyanatohexane, 1,8-diisocyanatooctane, 1,12-diisocyanatododecane, 1,5-diisocyanato-2-methylpentane, trimethyl-1,6-diisocyanatohexane, 1,3-bis(isocyanatomethyl)cyclohexane, trans-1,4-cyclohexene diisocyanate, 4,4'-methylenebis(cyclohexyl) isocyanate), isophorone diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, xylene-1,4-diisocyanate, tetramethylxylene-1,3-diisocyanate, 1-chloromethyl-2,4-diisocyanate, 4,4'-methylenebis(2,6-dimethylphenylisocyanate), 4,4'-oxybis(phenylisocyanate), trifunctional isocyanates derived from hexamethylene diisocyanate, and one or more selected from the group consisting of trimethylolpropane-added toluene diisocyanate.

[0062] More specifically, the urethane (meth)acrylate oligomer may be a compound each including two or more substituents represented by the following Chemical Formula 1 and a (meth)acryloyl group in a molecule.

[0063] [Chemical Formula 1]

[0064] *-OC(=O)NH-*

[0065] The urethane (meth)acrylate oligomer may be produced by reacting 1 mol of a diisocyanate represented by the following Chemical Formula 2 with 2 mol of a polymerizable unsaturated compound containing active hydrogen.

[0066] [Chemical Formula 2]

[0067] R1-OC(=O)NH-R3-NHC(=O)O-R2

[0068] In the formula, R1 and R2 are each independently a substituent including a (meth)acryloyl group derived from a polymerizable unsaturated compound containing active hydrogen, and R3 is a divalent substituent derived from diisocyanate.

[0069] Specific examples of the urethane (meth)acrylate oligomer include products obtained by reacting 2-hydroxyethyl (meth)acrylate and 2,4-toluene diisocyanate, reacting 2-hydroxyethyl (meth)acrylate and isophorone diisocyanate, reacting 2-hydroxybutyl (meth)acrylate and 2,4-toluene diisocyanate, reacting 2-hydroxybutyl (meth)acrylate and isophorone diisocyanate, reacting pentaerythritol tri(meth)acrylate and 2,4-toluene diisocyanate, reacting pentaerythritol tri(meth)acrylate and isophorone diisocyanate, reacting pentaerythritol tri(meth)acrylate and dicyclohexylmethane diisocyanate, reacting dipentaerythritol penta(meth)acrylate and isophorone diisocyanate, and reacting dipentaerythritol penta(meth)acrylate and dicyclohexylmethane diisocyanate.

[0070] Polyester (meth)acrylate can be produced by reacting polyester polyol and acrylic acid according to a method known in the art.

[0071] The polyester (meth)acrylate may be, for example, one or more selected from the group consisting of polyester acrylate, polyester diacrylate, polyester tetraacrylate, polyester hexaacrylate, polyester pentaerythritol triacrylate, polyester pentaerythritol tetraacrylate, and polyester pentaerythritol hexaacrylate, but is not limited thereto.

[0072] The photopolymerizable monomer and the photopolymerizable oligomer may be used alone or in combination. When the photopolymerizable monomer and the photopolymerizable oligomer are used in combination, the handleability and compatibility of the hard coating composition can be enhanced.

[0073] The content ratio of the photopolymerizable monomer to the photopolymerizable oligomer is not particularly limited and can be appropriately selected based on the storage modulus, shrinkage, and handleability of the hard coat layer. For example, the content ratio of the photopolymerizable oligomer to the photopolymerizable monomer can be between 1:10 and 10:1. If the content ratio of the photopolymerizable oligomer to the photopolymerizable monomer exceeds the above range, the storage modulus of the hard coat layer decreases, or the shrinkage increases, resulting in decreased hardness and flexibility, which may cause curling.

[0074] The content of the light-transmitting resin is not particularly limited, but can be, for example, 1 to 80 parts by weight, preferably 1 to 50 parts by weight, relative to 100 parts by weight of the hard coating composition. If the light-transmitting resin content is less than 1 part by weight, the elastic modulus of the hard coating layer decreases, and the hard coating layer may be prone to cracking when bent. If the light-transmitting resin content exceeds 80 parts by weight, the viscosity increases, coating properties decrease, and surface leveling is insufficient, which may cause problems with appearance characteristics.

[0075] To improve hardness and scratch resistance, the above-mentioned translucent resin may be used together with an inorganic nanofiller. The above-mentioned inorganic nanofiller may be a nanofiller having a diameter of generally less than 100 nm, preferably 10 to 100 nm, and more preferably 10 to 50 nm. Representative inorganic nanofillers include, for example, silica, alumina particles, titanium oxide particles, or zinc oxide particles, with silica being preferred. Silica may or may not have photocurable groups on its surface that can participate in photoreactions.

[0076] The inorganic nanofiller may be added by appropriately adjusting the content within a range that does not inhibit the effects of the present invention.

[0077] initiator

[0078] The above-mentioned initiator can be used without limitation as long as it is an initiator used in the present technical field. For example, one or more types selected from the group consisting of hydroxyketones, aminoketones, hydrogen abstraction type photoinitiators, and combinations thereof can be used.

[0079] Specifically, as the above-mentioned photoinitiator, one or more selected from the group consisting of 2-methyl-1-[4-(methylthio)phenyl]2-morpholinoacetone-1, diphenyl ketone, benzyl dimethyl ketal, 2-hydroxy-2-methyl-1-phenyl-1-one, 4-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxy-2-phenyl-acetophenone, anthraquinone, fluorene, triphenylamine, carbazole, 3-methylacetophenone, 4-chloroacetophenone, 4,4-dimethoxyacetophenone, 4,4-diaminobenzophenone, 1-hydroxycyclohexyl phenyl ketone, benzophenone, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, and combinations thereof can be used.

[0080] Such a photoinitiator is used in an amount of 0.1 to 10 parts by weight, preferably 0.3 to 5 parts by weight, based on 100 parts by weight of the total hard coating composition. If the content is less than the above range, the curing speed of the composition is slow, and the composition may not be cured, resulting in deterioration of mechanical properties. Conversely, if the content exceeds the above range, overcuring may cause cracks in the coating film.

[0081] solvent

[0082] The solvent can dissolve or disperse the above-mentioned composition, and any solvent known in the art for coating layer-forming compositions can be used without limitation.

[0083] As the solvent that can be used, preferably used are alcohols (methanol, ethanol, isopropanol, butanol, methyl cellosolve, ethyl cellosolve, etc.), ketones (methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, dipropyl ketone, cyclohexanone, etc.), acetates (ethyl acetate, propyl acetate, n-butyl acetate, tert-butyl acetate, methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, methoxybutyl acetate, methoxypentyl acetate, etc.), hexane (hexane, heptane, octane, etc.), benzene (benzene, toluene, xylene, etc.), ethers (diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, propylene glycol monomethyl ether, etc.). The above-mentioned solvents can be used alone or in combination of two or more.

[0084] Such a solvent can be used in an amount of 10 to 95 parts by weight per 100 parts by weight of the total hard coat composition, with the remainder being present excluding other components in the composition. If the solvent content is less than the above range, the viscosity is high, which not only reduces workability but also prevents sufficient swelling of the substrate film. Conversely, if the content exceeds the above range, the drying process requires a considerable amount of time, which reduces economic efficiency. Therefore, it is appropriate to use the solvent within the above range.

[0085] additive

[0086] In addition, the hard coat layer-forming composition for forming the hard coat layer of the present invention may further include, in addition to the above-mentioned components, one or more additives selected from the group consisting of a leveling agent, a UV stabilizer, and a heat stabilizer, and may further include additives commonly used in the technical field to which the present invention belongs. The content of these additives is adjusted in various ways within a range that does not degrade the physical properties of the hard coat layer-forming composition of the present invention, and is therefore not particularly limited.

[0087] A leveling agent is a component that imparts smoothness and coatability to a coating film. The leveling agent can be applied to any of the leveling agents commonly used in the art, such as silicone leveling agents, fluorine leveling agents, and acrylic polymer leveling agents. These can be used alone or in combination of two or more, but are not necessarily limited thereto. In order to reduce the contact angle and facilitate application of a low-refractive index layer to the hard coat layer, the hard coat layer according to one embodiment of the present invention preferably further includes a silicone or acrylic polymer additive to replace the compound containing a fluorine-based UV-curable functional group contained in the low-refractive index layer described later.

[0088] The leveling agent may be included in an amount of 0.1 to 1 part by weight based on 100 parts by weight of the hard coating composition, but is not limited thereto.

[0089] UV stabilizers are components that block or absorb ultraviolet light, preventing the cured hard coat layer from decomposing, discoloring, or breaking down when exposed to ultraviolet light. These UV stabilizers can be classified by their mechanism of action, such as absorbers, quenchers, and hindered amine light stabilizers (HALS); or by their chemical structure, such as phenyl salicylates (absorbers), benzophenones (absorbers), benzotriazoles (absorbers), nickel derivatives (matters), and radical scavengers. These can be used alone or in combination of two or more. There are no specific restrictions on the type of UV stabilizer, as long as it does not significantly alter the initial color of the hard coat layer.

[0090] As heat stabilizers, for example, commercially available polyphenol-based primary heat stabilizers and phosphate-based and lactone-based secondary heat stabilizers can be used alone or in combination. These can be used alone or in combination of two or more.

[0091] The UV stabilizer and heat stabilizer may be used in an appropriately adjusted amount at a level that does not affect UV curability. Specifically, the amount is preferably 0.1 to 3 parts by weight based on 100 parts by weight of the hard coating composition of the present invention.

[0092] The above-mentioned additives can be added by appropriately adjusting the content within a range that does not inhibit the effects of the present invention.

[0093] Low refractive layer 122

[0094] The low-refractive layer 122 can be manufactured by applying a low-refractive layer-forming composition onto the hard coating layer 121 and then curing the composition using light or heat, thereby imparting the properties of low reflectivity, excellent mechanical properties, and excellent wear resistance. In one embodiment of the present invention, the low-refractive layer-forming composition comprises a compound containing a fluorine-based UV-curable functional group, hollow silica particles, and nano-silica particles. The thickness of the low-refractive layer is 50 to 200 nm, and the value of the following formula 1, which calculates the ratio of the average particle diameters of the hollow silica particles and the nano-silica particles, can be 90 to 150%.

[0095] [Formula 1]

[0096] (B / A)*100(%)

[0097] In the above formula 1, A may be the average particle size of the hollow silica particles contained in the low-refractive layer-forming composition, and B may be the average particle size of the nano-silica particles contained in the low-refractive layer-forming composition.

[0098] In addition, the low-refractive layer 122 according to the present invention can be manufactured using a second hard coating layer-forming composition. The composition can include the compound containing a fluorine-based UV-curable functional group, hollow silica particles, and nano-silica particles, and can also include one or more selected from the group consisting of a light-transmitting resin, an initiator, and a solvent, and / or additives. The light-transmitting resin, initiator, solvent, and additives can be directly applied to the contents described in the description of the hard coating layer 121, and therefore their description is omitted.

[0099] Compounds containing fluorine-based UV-curable functional groups

[0100] The compound containing a fluorine-based UV-curable functional group is a component that adjusts the refractive index and imparts antifouling and wear resistance. It is necessary to contain fluorine, and there is no particular limitation as long as the compound has a UV-curable functional group. The above-mentioned compound containing a fluorine-based UV-curable functional group is included in the hard coating film formed on the polymer material, thereby increasing the initial water contact angle and reducing the refractive index, and can adjust the reflectivity and transmittance of the image display device to be described later. According to one embodiment of the present invention, the composition for forming the low-refractive layer formed on the hard coating layer includes a compound containing a fluorine-based UV-curable functional group, thereby increasing the initial water contact angle and wear resistance.

[0101] Specifically, the compound containing a fluorine-based UV-curable functional group can be an acrylate, methacrylate, vinyl, or the like containing a perfluorinated group. In this case, the compound containing a fluorine-based UV-curable functional group preferably has 1 to 6 UV-curable functional groups, but the scope of the present invention is not limited thereto. Any substance having a UV-curable functional group and containing a fluorinated group can be used.

[0102] According to one embodiment of the present invention, the compound containing a fluorine-based UV-curable functional group is preferably included in an amount of 0.01 to 30 parts by weight relative to 100 parts by weight of the total hard coat-forming composition. If the amount is less than 0.01 parts by weight, the initial contact angle is low, thereby reducing wear resistance. If the amount is greater than 30 parts by weight, mechanical properties such as the hardness of the film are reduced, thereby reducing wear resistance.

[0103] Hollow silica particles

[0104] According to an embodiment of the present invention, the low-refractive layer 122 may include hollow silica particles, and the refractive index of the hollow silica particles is 1.17 to 1.40.

[0105] The hollow silica particles are silicon-based microparticles with a low refractive index, which can reduce the reflectivity of the image display device described later. They are also optically transparent. In the present invention, a refractive index of 1.17 to 1.40 is advantageous in reducing reflectivity. Furthermore, the inclusion of the hollow silica particles provides a low dielectric constant in addition to optical properties, making them suitable for practical applications.

[0106] The average particle size of the hollow silica particles is 20 to 80 nm, preferably 20 to 70 nm, which is preferred in terms of composition processability and coating properties. The particle shape is preferably spherical, but not limited thereto.

[0107] The hollow silica particles are preferably contained in an amount of 0.1 to 20 parts by weight relative to 100 parts by weight of the total low-refractive-refractive-layer-forming composition, and more preferably 1 to 15 parts by weight in terms of reducing reflectivity and imparting excellent mechanical properties.

[0108] Nanosilica particles

[0109] According to one embodiment of the present invention, the low-refractive layer 122 may include nano-silica particles. The nano-silica particles and the hollow silica particles are also microparticles based on silicon, and can be characterized by an average particle size of more than 70 nm, preferably 80 to 130 nm, and more preferably 100 to 130 nm. When the above-mentioned particle size is met, the strength can be improved, and the light transmittance haze has the advantage of being reduced. The nano-silica particles may refer to particles that do not form holes on the surface and / or inside compared to the hollow silica particles, and can impart durability such as scratch resistance and wear resistance to the surface by being included in a low-refractive layer-forming composition.

[0110] When above-mentioned nano silica particles have the form with the dispersion liquid of solvent and are included in the composition, dispersibility improves and redisperses the advantage easily.As the solvent comprising in above-mentioned nano silica particles dispersion liquid, can use solvent as known in the art without restriction, can directly be suitable for the explanation of above-mentioned <hard coating 110> solvent, therefore omit record.Aspect the easiness of operation, relative to total 100 weight parts of nano silica particles dispersion liquid, nano silica particles can comprise 0.1 to 50 weight part, but is not limited to this.

[0111] The nano-silica particles are preferably contained in an amount of 0.1 to 20 parts by weight based on 100 parts by weight of the entire composition for forming a low-refractive layer, and more preferably 1 to 15 parts by weight in view of compatibility and light-transmitting haze characteristics.

[0112] The hard coat layer can be produced using methods known in the art. The thickness of the hard coat layer is not particularly limited, but may range from 5 to 30 μm, for example. The thickness of the low-refractive layer may range from 50 to 200 nm, preferably from 80 to 120 nm. When the thickness is within this range, the reflectivity of the substrate layer containing the hard coat layer can be easily controlled to 2 to 3%, thereby preventing fogging, which could affect the optical properties of the image display device described later. Conversely, if the low-refractive layer is thicker than the above range, the reflectivity may increase.

[0113] The hard coating film according to an embodiment of the present invention can be formed by applying a hard coating layer forming composition on a substrate and performing drying and UV curing steps to form a hard coating layer 121. Then, after applying a low-refractive layer forming composition on the hard coating layer 122, the low-refractive layer 122 is formed by performing drying and UV curing steps similar to the hard coating layer.

[0114] The step of drying the hard coating film may be performed by heating means such as a hot plate, hot air circulation, or ultraviolet rays, and may be performed at a temperature of 50 to 150°C or 50 to 100°C.

[0115] In the step of curing the hard coating film, irradiation is performed at 50 to 1000 mJ / cm 2 , preferably 200 to 800 mJ / cm 2 In particular, in the step of forming the hard coating 121, 50 to 600 mJ / cm 2 The first curing is performed at a relatively weak level, and in the step of forming the low refractive layer 122, 300 to 800 mJ / cm 2 The strong light intensity of UV is irradiated to further enhance the adhesion between the low refractive layer and the hard coating layer. When the hard coating layer and the low refractive layer are cured, the UV intensity of 300 to 600 mJ / cm 2 When the same amount of UV light is irradiated at the same level, the process can be simplified. As the light source used for irradiation, a low-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, an argon laser, etc. can be used. Depending on the situation, X-rays, electron beams, etc. can also be used.

[0116] <Image Display Device>

[0117] Figure 1 : is a diagram showing a stacked structure of a base material layer according to one embodiment of the present invention. Figure 1 , embodiments of the present invention provide a base material layer 100 including the hard coating film 120 and an image display device including the same.

[0118] For example, a hard coating film 120 in which the hard coating layer 121 and the low-refractive layer 122 are sequentially stacked may be formed on a substrate 110. In this case, the substrate layer 100 including the substrate 110 and the hard coating film 120 may be formed on the outermost surface or may be inserted into the interior of the image display device, depending on the needs of the image display device.

[0119] substrate 110

[0120] The substrate 110 functions to mitigate impact and / or scratch damage to the substrate layer surface, thereby preventing damage to the internal substrate. Materials with high deformation energy tolerance are preferred. Examples include release films formed from polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polybutylene naphthalate; polyamide resins; acrylic resins; styrene resins such as polystyrene and acrylonitrile-styrene; polycarbonate resins; polylactic acid resins; polyurethane resins; polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; vinyl resins such as polyvinyl chloride and polyvinylidene chloride; polyamide resins; sulfone resins; polyether-ether-ketone resins; allyl resins; cellulose resins such as triacetylcellulose; or mixtures of these resins. In one embodiment of the present invention, polyimide resins are most preferred due to their optical transparency, excellent resistance to friction, heat, and / or chemical damage, and excellent flexural properties.

[0121] The thickness of the substrate using the polyimide resin can be applied without limitation. However, the thicker the substrate, the lower the folding performance. Therefore, from the perspectives of foldability, transmittance, and durability, the thickness is preferably 30 to 100 μm.

[0122] The aforementioned image display device includes various image display devices, such as liquid crystal display devices, electroluminescent display devices, plasma display devices, and field emission display devices. It may be a flexible display device with flexibility and bendability, but is not limited thereto. In this case, the substrate layer 100, i.e., the hard coating stack, according to an embodiment of the present invention, utilizes the aforementioned configuration to reduce reflectivity and improve mechanical properties, thereby preventing fogging and controlling reflectivity to 2 to 3%. This allows for an image display device with excellent optical properties, a high initial water contact angle, and excellent durability, such as scratch resistance and abrasion resistance.

[0123] Implementation Method

[0124] The present invention will be described in more detail below based on examples. However, the embodiments of the present invention disclosed below are merely illustrative and the scope of the present invention is not limited to these embodiments. The scope of the present invention is indicated in the claims, and all modifications within the meaning and scope equivalent to those described in the claims are intended to be encompassed. In the following examples and comparative examples, "%" and "parts" indicating content are by weight unless otherwise specified.

[0125] Production Example 1: Production of a hard coat layer-forming composition

[0126] 52 parts by weight of a 9-functional urethane acrylate (Miwon Specialty Chemical, Miramer MU9800), 45 parts by weight of butyl acetate, 2.7 parts by weight of 1-hydroxycyclohexyl phenyl ketone, and 0.3 parts by weight of a silicone leveling agent (BYK, BYK-UV3530) were mixed using a blender and filtered through a PP filter to produce a hard coat layer-forming composition.

[0127] Production Examples 2 to 9: Production of Compositions for Forming Low-Refractive Layer

[0128] Production Example 2

[0129] 1.4 parts by weight of pentafunctional urethane acrylate (UA-306I, Kyoei Co., Ltd.), 93 parts by weight of methyl ethyl ketone, 0.1 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a compound containing a fluorine-based UV-curable functional group (DAC-H, Daikin Co., Ltd.), 3 parts by weight of hollow silica with an average particle size of 60 nm, and 2 parts by weight of a nanoparticle silica sol with an average particle size of 85 nm (MEK-AC-5140Z, Nissan Chemical Co., Ltd.) dispersed in methyl ethyl ketone were mixed in a blender and filtered through a PP filter to produce a composition for forming a low refractive index layer.

[0130] Production Example 3

[0131] 1.4 parts by weight of pentafunctional urethane acrylate (UA-306I, Kyoei Co., Ltd.), 93 parts by weight of methyl ethyl ketone, 0.1 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a fluorine-containing UV-curable functional group-containing compound (DAC-HP, Daikin Co., Ltd.), 3 parts by weight of hollow silica with an average particle size of 60 nm, ethanol, and 2 parts by weight of a nanoparticle silica sol with an average particle size of 85 nm (VPS KE 80, Evonik Co., Ltd.) dispersed in ethylhexanol were mixed in a blender and filtered through a PP filter to produce a composition for forming a low-refractive layer.

[0132] Production Example 4

[0133] 1.4 parts by weight of pentafunctional urethane acrylate (UA-306I, Kyoei Co., Ltd.), 93 parts by weight of methyl ethyl ketone, 0.1 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a compound containing a fluorine-based UV-curable functional group (DAC-HP, Daikin Co., Ltd.), 3 parts by weight of hollow silica with an average particle size of 50 nm, and 2 parts by weight of a nanoparticle silica sol with an average particle size of 45 nm (PGM-AC-4130, Nissan Chemical Co., Ltd.) dispersed in propylene glycol monomethyl ether were mixed in a blender and filtered through a PP filter to produce a composition for forming a low-refractive layer.

[0134] Production Example 5

[0135] 1.4 parts by weight of pentafunctional urethane acrylate (UA-306I, Kyoei Co., Ltd.), 93 parts by weight of methyl ethyl ketone, 0.1 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a compound containing a fluorine-based UV-curable functional group (DAC-HP, Daikin Co., Ltd.), 3 parts by weight of hollow silica with an average particle size of 60 nm, and 2 parts by weight of a nanoparticle silica sol with an average particle size of 12 nm (MEK-ST-40, Nissan Chemical Co., Ltd.) dispersed in methyl ethyl ketone were mixed in a blender and filtered through a PP filter to produce a composition for forming a low refractive index layer.

[0136] Production Example 6

[0137] A low-refractive-layer-forming composition was prepared by mixing 1.4 parts by weight of a pentafunctional urethane acrylate (UA-306I, Kyoei Co., Ltd.), 93 parts by weight of methyl ethyl ketone, 0.1 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a compound containing a fluorine-based UV-curable functional group (DAC-HP, Daikin Co., Ltd.), 3 parts by weight of hollow silica with an average particle size of 60 nm, and 2 parts by weight of a nanoparticle silica sol with an average particle size of 45 nm (PGM-AC-4130Y, Nissan Chemical Co., Ltd.) dispersed in propylene glycol monomethyl ether using a blender and filtering through a PP filter.

[0138] Production Example 7

[0139] 1.4 parts by weight of pentafunctional urethane acrylate (UA-306I, Kyoei Co., Ltd.), 93 parts by weight of methyl ethyl ketone, 0.1 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a compound containing a fluorine-based UV-curable functional group (DAC-HP, Daikin Co., Ltd.), and 3 parts by weight of hollow silica having an average particle size of 60 nm were mixed in a blender and filtered through a PP filter to produce a composition for forming a low-refractive layer.

[0140] Production Example 8

[0141] 1.4 parts by weight of pentafunctional urethane acrylate (UA-306I, Kyoei Co., Ltd.), 93 parts by weight of methyl ethyl ketone, 0.1 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a compound containing a fluorine-based UV-curable functional group (DAC-HP, Daikin Co., Ltd.), 3 parts by weight of hollow silica with an average particle size of 60 nm, and 2 parts by weight of nanoparticle silica sol with an average particle size of 100 nm (SS-SOL 100, S-Chemtech Co., Ltd.) were mixed in a blender and filtered through a PP filter to produce a composition for forming a low-refractive layer.

[0142] Production Example 9

[0143] 1.4 parts by weight of a pentafunctional urethane acrylate (UA-306I, Kyoei Co., Ltd.), 93 parts by weight of methyl ethyl ketone, 0.1 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a silicone leveling agent (BYK-307, BYK), 3 parts by weight of hollow silica with an average particle size of 60 nm, and 2 parts by weight of a nanoparticle silica sol with an average particle size of 80 nm (MEK-AC-5140Z, Nissan Chemical) dispersed in methyl ethyl ketone were mixed in a blender and filtered through a PP filter to produce a composition for forming a low refractive index layer.

[0144] Examples 1 to 5 and Comparative Examples 1 to 4: Preparation of Hard Coating Films and Substrate Layers Including the Hard Coating Films

[0145] Example 1

[0146] On a polyimide film (PI, 50 μm), the hard coat layer-forming composition prepared in Preparation Example 1 was applied to a thickness of 10 μm after curing, the solvent was dried, and the film was irradiated with UV light at a cumulative dose of 500 mJ / cm 2 After forming a hard coat layer, the low refractive layer forming composition of the above-mentioned manufacturing example 2 was applied thereon in such a manner that the thickness after curing became 100 nm, the solvent was dried, and UV cumulative light was irradiated in a nitrogen atmosphere at a dose of 500 mJ / cm2 , a base layer in which a hard coating film is laminated on a base material is manufactured.

[0147] Example 2

[0148] On a polyimide film (PI, 50 μm), the hard coat layer-forming composition prepared in Preparation Example 1 was applied to a thickness of 10 μm after curing, the solvent was dried, and the film was irradiated with UV light at a cumulative dose of 500 mJ / cm 2 After forming a hard coat layer, the composition for forming a low refractive layer of the above-mentioned manufacturing example 3 was applied thereon in such a manner that the thickness after curing became 100 nm, the solvent was dried, and UV cumulative light was irradiated in a nitrogen atmosphere at a dose of 500 mJ / cm 2 , a base layer in which a hard coating film is laminated on a base material is manufactured.

[0149] Example 3

[0150] On a polyimide film (PI, 50 μm), the hard coat layer-forming composition prepared in Preparation Example 1 was applied to a thickness of 10 μm after curing, the solvent was dried, and the film was irradiated with UV light at a cumulative dose of 500 mJ / cm 2 After forming a hard coat layer, the composition for forming a low refractive layer of the above-mentioned manufacturing example 4 was applied thereon in such a manner that the thickness after curing became 100 nm, the solvent was dried, and UV cumulative light was irradiated in a nitrogen atmosphere at a dose of 500 mJ / cm 2 , a base layer in which a hard coating film is laminated on a base material is manufactured.

[0151] Comparative Example 1

[0152] On a polyimide film (PI, 50 μm), the hard coat layer-forming composition prepared in Preparation Example 1 was applied to a thickness of 10 μm after curing, the solvent was dried, and the film was irradiated with UV light at a cumulative dose of 500 mJ / cm 2 After forming a hard coat layer, the composition for forming a low refractive layer of the above-mentioned manufacturing example 5 was applied thereon in such a manner that the thickness after curing became 100 nm, the solvent was dried, and UV cumulative light was irradiated in a nitrogen atmosphere at a dose of 500 mJ / cm 2 , a base layer in which a hard coating film is laminated on a base material is manufactured.

[0153] Comparative Example 2

[0154] On a polyimide film (PI, 50 μm), the hard coat layer-forming composition prepared in Preparation Example 1 was applied to a thickness of 10 μm after curing, the solvent was dried, and the film was irradiated with UV light at a cumulative dose of 500 mJ / cm 2After forming a hard coat layer, the low refractive layer forming composition of Manufacturing Example 6 was applied thereon in such a manner that the thickness after curing became 100 nm, the solvent was dried, and UV cumulative light was irradiated in a nitrogen atmosphere at a dose of 500 mJ / cm 2 , a base layer in which a hard coating film is laminated on a base material is manufactured.

[0155] Comparative Example 3

[0156] On a polyimide film (PI, 50 μm), the hard coat layer-forming composition prepared in Preparation Example 1 was applied to a thickness of 10 μm after curing, the solvent was dried, and the film was irradiated with UV light at a cumulative dose of 500 mJ / cm 2 After forming a hard coat layer, the low refractive layer forming composition of Manufacturing Example 7 was applied thereon in such a manner that the thickness after curing became 100 nm, the solvent was dried, and UV cumulative light was irradiated in a nitrogen atmosphere at a dose of 500 mJ / cm 2 , a base layer in which a hard coating film is laminated on a base material is manufactured.

[0157] Comparative Example 4

[0158] On a polyimide film (PI, 50 μm), the hard coat layer-forming composition prepared in Preparation Example 1 was applied to a thickness of 10 μm after curing, the solvent was dried, and the film was irradiated with UV light at a cumulative dose of 500 mJ / cm 2 After forming a hard coat layer, the composition for forming a low refractive layer of the above-mentioned manufacturing example 8 was applied thereon in such a manner that the thickness after curing became 100 nm, the solvent was dried, and UV cumulative light was irradiated in a nitrogen atmosphere at a dose of 500 mJ / cm 2 , a base layer in which a hard coating film is laminated on a base material is manufactured.

[0159] Comparative Example 5

[0160] On a polyimide film (PI, 50 μm), the hard coat layer-forming composition prepared in Preparation Example 1 was applied to a thickness of 10 μm after curing, the solvent was dried, and the film was irradiated with UV light at a cumulative dose of 500 mJ / cm 2 After forming a hard coat layer, the low refractive layer forming composition of the above-mentioned manufacturing example 2 was applied thereon in such a manner that the thickness after curing became 300 nm, the solvent was dried, and UV cumulative light was irradiated in a nitrogen atmosphere at a dose of 500 mJ / cm 2 , a base layer in which a hard coating film is laminated on a base material is manufactured.

[0161] Comparative Example 6

[0162] On a polyimide film (PI, 50 μm), the hard coat layer-forming composition prepared in Preparation Example 1 was applied to a thickness of 10 μm after curing, the solvent was dried, and the film was irradiated with UV light at a cumulative dose of 500 mJ / cm 2 After forming a hard coat layer, the composition for forming a low refractive layer of the above-mentioned manufacturing example 9 was applied thereon in such a manner that the thickness after curing became 100 nm, the solvent was dried, and UV cumulative light was irradiated in a nitrogen atmosphere at a dose of 500 mJ / cm 2 , a base layer in which a hard coating film is laminated on a base material is manufactured.

[0163] The manufacturing examples, coating film thickness, particle sizes of the hollow silica particles and nano silica particles contained in the low-refractive layer, and the values ​​calculated by applying them to Formula 1, respectively, applied in Examples 1 to 3 and Comparative Examples 1 to 6, are as shown in Table 1 below.

[0164]

Table 1

[0165]

[0166] Experimental example

[0167] The physical properties of the base material layers produced in Examples 1 to 3 and Comparative Examples 1 to 6 were measured by the following methods. The results are shown in Table 2.

[0168] (1) Determination of water contact angle

[0169] The water contact angle was measured using a contact angle meter DSA100 manufactured by KRUSS Corporation at room temperature with a droplet volume of 3 μl.

[0170] (2) Determination of Haze

[0171] The haze of the substrate layers of the above-mentioned Examples and Comparative Examples was measured using a haze meter (HM-2, Murakami Co., Ltd.).

[0172] (3) Determination of reflectivity

[0173] The base material layers produced in the above Examples and Comparative Examples were bonded to a black acrylic resin plate, and after eliminating back reflection, the reflectance was measured using an integrating sphere reflectance analyzer (CM-3700A, Konica Minolta).

[0174] (4) Scratch resistance

[0175] After fixing the substrate layer to the glass with the hard coating facing upward, steel wool (#0000) was used to polish the glass at a speed of 250 g / cm 2 After rubbing the film back and forth 10 times with a load of 10, the presence or absence of scratches on the film surface was confirmed. The results are shown in Table 2 below based on the following evaluation criteria.

[0176] <Evaluation Criteria>

[0177] ○: No scratches

[0178] △: 20 or fewer scratches (hardly visible to the naked eye)

[0179] X: More than 20 scratches, a large number of scratches

[0180] (5) Wear resistance

[0181] The measurement was performed using an abrasion tester manufactured by Daesung Precision Co. The coated surface was rubbed 1000 times with an eraser and a 500 g weight, and then the water contact angle was measured. The results are shown in Table 2 below based on the following evaluation criteria.

[0182] <Evaluation Criteria>

[0183] ○: Contact angle 100° or more

[0184] X: Contact angle less than 100°

[0185]

Table 2

[0186]

[0187]

[0188] According to the experimental data in Table 2 above, the results of evaluating the physical properties of the substrate layer manufactured in Examples 1 to 3 of the present invention showed that the initial water contact angle was large, the haze value was low, the reflectivity was greater than 2% and less than 3%, and excellent results were shown in both the scratch resistance and wear resistance evaluations.

[0189] On the contrary, in the case of Comparative Example 3 in which a low-refractive layer-forming composition not containing nano-silica particles was used, and Comparative Examples 1, 2, and 4 in which the value of Formula 1 was less than 90% or greater than 150%, and Comparative Example 5 in which the thickness of the low-refractive layer was greater than 200nm, the results of any one or more of the above-mentioned initial water contact angle, haze, reflectivity, and abrasion resistance evaluations showed poor results that did not reach the examples of the present invention. The initial water contact angle of Comparative Example 6 in which a compound containing a fluorine-based UV-curable functional group was not included in the low-refractive layer-forming composition was particularly low. In addition, unlike the examples of the present invention, a large number of scratches were observed in all of Comparative Examples 1 to 6 that were not based on an embodiment of the present invention.

[0190] Therefore, according to one embodiment of the present invention, the hard coating film includes a low-refractive layer formed on the hard coating layer, and the composition forming the low-refractive layer includes a compound containing a fluorine-based UV-curable functional group, hollow silica particles, and nano-silica particles. The thickness of the low-refractive layer is 50 to 200 nm. When the ratio of the average particle size of the hollow silica particles to the average particle size of the nano-silica particles satisfies 90 to 150%, the reflectivity can reach 2% or more and less than 3%, while maintaining excellent mechanical properties.

[0191] Industrial applicability

[0192] The hard coating film according to the present invention can control the reflectivity to be 2% or more and less than 3%.

Claims

1. A hard coating film, characterized in that: include: Hard coating, and a low refractive layer formed on the hard coating layer, The low-refractive layer is formed from a low-refractive layer-forming composition, The low-refractive layer-forming composition comprises a compound containing a fluorine-based UV-curable functional group, hollow silica particles, and nano-silica particles. The thickness of the low refractive layer is 50 to 200 nm, The value of the following formula 1 is 90 to 150%, [Formula 1] (B / A)*100(%) In the formula 1, A is the average particle size of the hollow silica particles contained in the low-refractive layer-forming composition, B is the average particle size of the nano-silica particles contained in the composition for forming the low-refractive layer.

2. The hard coating film according to claim 1, wherein The compound containing a fluorine-based UV-curable functional group contains 1 to 6 UV-curable functional groups in a molecule.

3. The hard coating film according to claim 1, wherein The hard coating film has a reflectivity of 2% or more and less than 3%.

4. The hard coating film according to claim 1, wherein The hard coat layer and the low refractive layer are formed on one or more substrates selected from release films formed of polyester resins, polyamide resins, acrylic resins, styrene resins, polycarbonate resins, polylactic acid resins, polyurethane resins, polyolefin resins, vinyl resins, polyamide resins, sulfone resins, polyether-ether-ketone resins, allyl compound resins, cellulose resins, and mixtures thereof.

5. The hard coating film according to claim 1, wherein The low-refractive layer-forming composition further includes one or more selected from the group consisting of a light-transmitting resin, an initiator, and a solvent.

6. The hard coating film according to claim 1, wherein The refractive index of the hollow silica particles is 1.17 to 1.

40.

7. The hard coating film according to claim 6, wherein The hollow silica particles are contained in an amount of 0.1 to 20 parts by weight based on 100 parts by weight of the entire composition for forming a low-refractive layer.

8. The hard coating film according to claim 1, wherein The average particle size of the nano-silicon dioxide particles is 80 to 130 nm.

9. The hard coating film according to claim 1, wherein The low-refractive layer-forming composition further contains, as an additive, one or more selected from the group consisting of a leveling agent, an ultraviolet stabilizer, and a heat stabilizer. 10 . An image display device comprising the hard coating film according to claim 1 .